Providing HIV Prevention of Mother to Child Transmission (PMTCT) Services to Migrants During the COVID-19 Pandemic in South Africa: Insights of Healthcare Providers. - Bisnauth, Melanie A; Coovadia, Ashraf; Kawonga, Mary; Vearey, Jo (Health Services Insights, 2022)
Background: In March 2020, COVID-19 entered South Africa, resulting in 2.9 million cases, the country took preventative and precautionary measures to control the spread of COVID-19 infection. These measures limited population mobility especially for migrant women living with HIV (WLWH) and the provision of PMTCT services. The purpose of this research was to explore the challenges of the COVID-19 pandemic on PMTCT provision by healthcare providers and understand what strategies could be implemented with lifelong antiretroviral therapy (ART) for migrants to better manage the program. Methods: Twelve in-depth interviews were conducted with healthcare providers across city and provincial levels on how the changes to the healthcare system with COVID-19 affected highly mobile patients' adherence and utilization of PMTCT services. A thematic content analysis was used for emerging themes and guided by The Utilization of PMTCT Services conceptual framework. Results: Five main themes emerged: (1) Facilitators and barriers to adherence, which included the need for multi-month dispensing for the long term supply of antiretrovirals (ARVs) and the fear of contracting COVID-19 at the hospital that disrupted patients' continuum of care; (2) Healthcare providers work environment, where participants felt overwhelmed with the high patient demand and the lack of infrastructural resources to follow social distancing protocols; (3) Financial challenges and opportunity costs, PMTCT proved difficult for migrants due to border closures and documentation required to receive care, this resulted in treatment interruption and left many unable to receive support at the facility due to capacity restrictions; (4) Interpersonal interactions, mistreatment, and xenophobic attitudes existed toward the migrant HIV population; and (5) "Program sustainability" revealed three key areas for strengthening: longer duration of time allocated with counseling for same-day initiation, the increased use of technology, and translation services for migrants. Conclusions: It is important to take what was learned during the pandemic and integrate it into routine service delivery, which includes long-term medication supply to reduce risk with multiple visits to collect medication, and the use of technology to alleviate the high-burden of patient demand. Healthcare policies that work toward inclusion and sustainability for migrants are needed to improve the integration of safer and practical methods of PMTCT provision into health systems.